Boreal earliest Triassic biotas elucidate globally depauperate hard substrate communities after the end-Permian mass extinction - Zatoń, Michał (Sci Rep, 2016)
The end-Permian mass extinction constituted the most devastating biotic crisis of the Phanerozoic. Its aftermath was characterized by harsh marine conditions incorporating volcanically induced oceanic warming, widespread anoxia and acidification. Bio-productivity accordingly experienced marked fluctuations. In particular, low palaeolatitude hard substrate communities from shallow seas fringing Western Pangaea and the Tethyan Realm were extremely impoverished, being dominated by monogeneric colonies of filter-feeding microconchid tubeworms. Here we present the first equivalent field data for Boreal hard substrate assemblages from the earliest Triassic (Induan) of East Greenland. This region bordered a discrete bio-realm situated at mid-high palaeolatitude (>30°N). Nevertheless, hard substrate biotas were compositionally identical to those from elsewhere, with microconchids encrusting Claraia bivalves and algal buildups on the sea floor. Biostratigraphical correlation further shows that Boreal microconchids underwent progressive tube modification and unique taxic diversification concordant with changing habitats over time. We interpret this as a post-extinction recovery and adaptive radiation sequence that mirrored coeval subequatorial faunas, and thus confirms hard substrate ecosystem depletion as a hallmark of the earliest Triassic interval globally.